Thai Consumer Organic Food-Related Lifestyle (FRL), Attitude and Perceived Value Segmentation: A Discriminant Analysis Approach - Nuttakit Jetsadalak; Opal Suwunnamek (My University, 2018)
Background and Objective: Thailand is becoming a key participant in the global production of organic food products.As such, the objectives of this study were to examine the antecedents and consequences of Thai consumer attitudes toward local organic food products and to segment these consumers using their food-related lifestyle (FRL) patterns, attitudes and perceived values.Materials and Methods: This research employed quantitative methods and use of a 72 item questionnaire to collect data from 400 Thai organic food consumers in the first half of 2018.SPSS software version 21 was used to conduct a cluster analysis and discriminant analysis and then analyze the frequencies, percentage, mean and standard deviation.Results: From the segmentation into three organic food consumer groups, which included sensory organic eaters (Group 1), organic eaters (Group 2) and unhealthy conventional organic eaters (Group 3), it was determined that an organic food productʼs quality aspect had the greatest importance across all three groups.However, a consumerʼs attitude concerning their emotional value was judged to have the least importance across all three groups when purchasing organic food products (OFP).Conclusion: From the analysis of the three groups of Thai organic food consumers, the sensory organic eaters (SOEs = Group 1) and the organic eaters (Oes = Group 2) were highly sensitive and had nearly the same attributes to each other.Perceived value, attitude and food-related lifestyle were also shown to be helpful in separating the unhealthy conventional organic eaters (UCOEs = Group 3) for marketing purposes.Finally, consumers of organic food products in all three groups placed a very high value on sanitary and phytosanitary conditions.
Keywords: Value (mathematics); Organic Food and Agriculture